Dust - Tolange, Deepak (Nepal, 2016)
Every winter thousands of Nepalis and Indians migrate to various parts of Nepal to work in brick factories. Many of these laborers are children who leave their homes and schools, some forever, to engage in hard labor. This ethnographic film asks the children working in the brick kilns of Nepal about their dreams and desires.
Keywords: Documentary films